Trust evaluation using fuzzy proximity relation with ordering for MANET. (1st January 2013) - Senthil Kumar, K.; Acharjya, D.P.; Thangavelu, Arunkumar
Nodes in a MANET would face difficulties in identifying the trusted nodes for efficient communication with the available information. Establishing a trusted path for efficient communication is highly challenging since the presence of vagueness exists among nodes. Accordingly nodes need a significant trust evaluation process, which would classify the trusted and un-trusted nodes in a MANET. In this paper, we propose a trust evaluation model that uses a fuzzy proximity relation with ordering. The fuzzy proximity relation classifies the nodes based on almost similarity using nodes metric. On introducing ordering we identify the trust level of nodes. Then the communication would be established through the trusted nodes. Finally, we have compared our proposed model with AODV. The comparison results show the viability of our proposed model.